Вы находитесь на странице: 1из 16

()

, 2007

, .
.
XVII . 1,
. 2, . , . . 1659 .
3
. . .-. 70 XVII
.

.
.-. y dx ,
( s ) summa (), y dx
. .-. 4

, y dx .
a

x .

. . .. 5 ..
6 .
,
.
.

(15911647) , .
(16081647) , .
3
(16301677) , .
4
(17681830) ,
.
5
(18011861)
; .
6
(18211894) ,
; .
2

1.

x
+ C , n 1 ( n = 1 . 1.2)
n +1

1.

2.

x = ln x + C ,
e dx = e + C

3.

dx =

dx
x

()

n +1

x0

ax
+C
ln a
5. sin xdx = cos x + C
4.

x
a dx =

6.

cos xdx = sin x + C

7.

cos

8.

sin

9.

10.

11.
12.
13.
14.

dx
2

dx

= ctg x + C

x
dx

= tg x + C

1 x2
dx
2

= arcsin x + C
= arcsin

x
+C
a

a x
dx
1 + x 2 = arctg x + C
dx
x
a 2 + x 2 = arctg a + C
dx
2
2
x 2 a 2 = ln x + x a + C
tg xdx = ln cos x + C

15. ctg xdx = ln sin x + C

dx

dx

16.

sin x = ln tg 2

17.

cos x = ln tg 2 + 4 + C = ln sec x tg x + C

18.

+ C = ln cosec x ctg x + C

dx
1
xa
=
ln
+C
2
a
2a x + a
2.
dx

, a + bx ( b 0 )

1.

a + bx = b ln a + bx + C

2.

(a + bx )

dx

1
b(a + bx )

3.

(a + bx )
n
(a + bx ) dx = b(n + 1)

4.

x dx
1
a + bx = b [a + bx a ln a + bx ]+ C

n +1

+C

5.
6.
7.
8.

1 1
x 2 dx

2
2
a + bx = b 3 2 (a + bx ) 2a(a + bx ) + a ln a + bx + C
dx
1 a + bx
x(a + bx ) = a ln x + C
dx
1
b
a + bx
x 2 (a + bx ) = ax + a 2 ln x + C
x dx
1
a
(a + bx )2 = b 2 ln a + bx + a + bx + C

a2
1
a + bx 2a ln a + bx
=
9.
+C
a + bx
(a + bx )2 b 3
dx
a + bx
1
1
=
2 ln
+C
10.
2
a(a + bx ) a
x
x(a + bx )
x 2 dx

11.

x dx

(a + bx )

a
1
1

+C
2
2
b 2(a + bx ) a + bx

, a 2 + x 2 , a 2 x 2 , a + bx 2

3.
1.
2.
3.
4.
5.

dx

1+ x

= arctg x + C

dx
x
1
= arctg + C
2
+x
a
a
1 a+x
dx
a 2 x 2 = 2a ln a x + C
1
dx
x+a
a 2 x 2 = 2a ln x a + C
dx
1
b
a + bx 2 = ab arctg x a + C , a > 0 b > 0 . a b ,
() , a b ,
3.6.

dx

6.

a bx

7.

a + bx

x dx

=
=

1
2 ab

ln

ab + bx
ab bx

+ C , ab > 0

1 2 a
ln x + + C
2b
b

x 2 dx
x a
dx
a + bx 2 = b b a + bx 2 , 3.5 3.6.
dx
1
x2
9.
=
ln
+C
x a + bx 2
2a a + bx 2
dx
1 b
dx
10. 2
, 3.5 3.6.
=
2
x a + bx
ax a a + bx 2
dx
x
1
dx
11.
, 3.5 3.6.
=
+
2

2 2
2a a + bx
2a a + bx 2
a + bx
8.

4.
2
3b

1.

2.

x a + bx dx =

3.

2
x a + bx dx =

4.
5.
6.
7.

a + bx dx =

dx
a + bx
x dx
a + bx
x 2 dx
a + bx
Mx + N
a + bx

a + bx .

(a + bx )3 + C
2(2a 3bx ) (a + bx )
+C
15b 2
3

2 8a 2 12abx + 15b 2 x 2

) (a + bx )

105b 3

+C

2
a + bx + C
b
2(2a bx )
=
a + bx + C
3b 2

2 8a 2 4abx + 3b 2 x 2
a + bx + C
15b3
2
dx = 2 (3 Nb 2 Ma + Mbx ) a + bx + C
3b
=

8.

dx
1
a + bx a
=
ln
+ C a > 0 .
a + bx
a
a + bx + a

9.

dx
a + bx
2
=
+ C a < 0 .
arctg
a
a
a + bx

10.

11.

a + bx dx
dx
, 4.8 4.9.
= 2 a + bx + a
x
x a + bx

dx
a + bx b
dx
, 4.8 4.9.
=

ax
2a x a + bx
a + bx

5.

x2 + a2

x
a2
x2 + a2 +
ln x + x 2 + a 2 + C
2
2
3a 4
x
dx = 2 x 2 + 5a 2 x 2 + a 2 +
ln x + x 2 + a 2 + C
8
8

1.

2.

(x

3.

4.

2
2
2
x x + a dx =

5.

6.

7.

x 2 + a 2 dx =
2

+ a2

(x

x + a dx =

dx
2

x +a
dx

(x

+a
x dx
2

x +a

+ a2
3

+C

x
2 x2 + a2
8

x2 + a2

= ln x + x 2 + a 2 + C

2 3

x
a

x2 + a2

= x2 + a2 + C

+C

a4
ln x + x 2 + a 2 + C
8

8.

9.

10.

11.
12.
13.
14.

x 2 dx
x2 + a2
x 2 dx

(x

+a
dx

2 3

)
x + a )+ C

x +a

x
1
ln
+C
a a + x2 + a2

x2 + a2

(
+ ln (x +

x 2
a2
x + a 2 ln x + x 2 + a 2 + C
2
2

x2 + a2
=
+C
a2 x
x2 + a2
dx

dx
3

x2 + a2
1
a + x2 + a2
+
+C
ln
2a 2 x 2
2a 3
x

x2 + a2

x2 + a2
a + x2 + a2
dx = x 2 + a 2 a ln
+C
x
x

x2 + a2
x2 + a2
dx
=

+ ln x + x 2 + a 2 + C
2
x
x
6.

1.

2.

3.

4.

5.

dx

= arcsin

a2 x2
dx

x2
x dx

a x
x dx

(a

a2 a2 x2

x dx

2 3

a2 x2

7.

8.

(a

9.

10.

x (a

11.

2
2
2
x a x dx =

a2 x2

a 2 x 2 dx =

x
dx = 5a 2 2 x 2
8

2 3

+C

x
a2
x
a2 x2 +
arcsin + C
a
2
2

a x dx =
2

+C

x 2
a2
x
a x 2 + arcsin + C
2
2
a

6.

x
+C
a
x

= a2 x2 + C

a2 x2

= arcsin x + C

1 x2
dx

(a

2 3

(a

dx =

x2
3

(a

x2
5

x
2x2 a2
8

3a 4
x
a x +
arcsin + C
8
a
2

+C

+C

a2 x2 +

a4
x
arcsin + C
8
a

12.

13.

14.
15.
16.
17.

x 2 dx

(a

x
dx

a2 x2

2 3

a x

arcsin

x
+C
a

x
1
ln
+C
a a + a2 x2

a2 x2
=
+C
a2 x
a2 x2
dx

dx
3

a2 x2
1
x
+ 3 ln
+C
2 2
2a x
2a
a + a2 x2

a2 x2

a2 x2
a + a2 x2
dx = a 2 x 2 a ln
+C
x
x

a2 x2
a2 x2
x
dx
=

arcsin + C
2
x
a
x

7.

2.

3.

4.

5.

(x

6.

7.

x (x

x a
dx

(x

x a

= ln x + x 2 a 2 + C

a
x dx

2 3

x
a2 x2 a2

+C

= x2 a2 + C

a2

x a dx =
2

x 2
a2
x a 2 ln x + x 2 a 2 + C
2
2
3a 4
x
dx = 2 x 2 5a 2 x 2 a 2 +
ln x + x 2 a 2 + C
8
8

x 2 a 2 dx =
2

x2 a2

dx

1.

2 3

(x

a2
3

(x

dx =

a2
5

+C

+C

x
a4
2 x 2 a 2 x 2 a 2 ln x + x 2 a 2 + C
8
8
2
2
x dx
x 2
a
9.
=
x a 2 + ln x + x 2 a 2 + C
2
2
2
2
x a
2
x dx
x
10.
=
+ ln x + x 2 a 2 + C
3
2
2
x a
x2 a2
dx
11.
= arcsec x + C
x x2 a2
dx
x
1
12.
= arcsec + C
2
2
a
a
x x a
8.

2
2
2
x x a dx =

13.
14.
15.
16.

dx
2

x2 a2

dx
3

x2 a2

x2 a2
+C
a2 x

x2 a2
1
x
+ 3 arcsec + C
2 2
2a x
2a
a

x2 a2
a
dx = x 2 a 2 a arccos + C
x
x

x2 a2
x2 a2
dx =
+ ln x + x 2 a 2 + C
2
x
x

8.

,
2ax x 2

9.

2ax + x 2

2ax x 2 , t = x a .

a 2 t 2 , 6 .

2ax + x 2

2ax x 2 ,

2ax + x 2 , t = x + a .

t 2 a 2 , 7 .
, a + bx + cx 2 ( c > 0 )

1.

2
2cx + b

arctg
+ C , b 2 < 4ac
2
2
4ac b
4ac b

dx
2

2
a + bx + cx 2 = 2cx + b + C , b = 4ac

1
2cx + b b 2 4ac

ln
+ C , b 2 > 4ac
2
2
b 4ac 2cx + b + b 4ac

2.

1
ln 2cx + b + 2 c a + bx + cx 2 + C , c > 0

dx
c
=
a + bx + cx 2 1 arcsin 2cx + b + C , c < 0
c
b 2 4ca

3.

a + bx + cx 2 dx =

4.

5.

2cx + b
b 2 4ac
ln 2cx + b + 2 c a + bx + cx 2 + C
a + bx + cx 2
3
4c
8 c

9.2.
6.

a + bx + cx 2
b
=

ln 2cx + b + 2 c a + bx + cx 2 + C
2
3
c
2 c
a + bx + cx
Mx + N
M
dx
2cN Mb
dx =
a + bx + cx 2 +

c
2c
a + bx + cx 2
a + bx + cx 2
x dx

Mx + N

a + bx + cx

dx =

M
dx
2cN Mb
ln a + bx + cx 2 +

2c
a + bx + cx 2
2c

7.

8.

9.1.
dx
dx
2cx + b
2(2n 3)c
a + bx + cx 2 n = (n 1) 4ca b2 a + bx + cx 2 n1 + (n 1) 4ca b2 a + bx + cx2
n 1 .
,
9.1.

Mx + N

(a + bx + cx )

2 n

dx =

)(

2(n 1)c a + bx + cx

2 n 1

2cN bM
2c

) (

2 n 1

n 1 .
, 9.1.
10. , a + bx cx 2 ( c > 0 )

1.
2.

3.

4.

dx

1
2cx b
arcsin
+C
2
2
c
a + bx cx
b + 4ac
2cx b
2cx b
b 2 + 4ac
arcsin
a + bx cx 2 dx =
a + bx + cx 2 +
+C
4c
8 c3
b 2 + 4ac
=

x dx
a + bx cx 2

a + bx cx 2
b
2cx b
+
+C
arcsin
c
2 c3
b 2 + 4ac

11.
1.

2.

a+x
dx =
b+x
ax
dx =
b+ x

3.

a+x
bx
dx = (a + x )(b x ) (a + b )arcsin
+C
bx
a+b

4.

1+ x
dx = 1 x 2 + arcsin x + C
1 x

5.

(x a )(b x ) = 2 arcsin

6.

(x + a )(x + b ) = a b ln x + a + C , a b

7.

(ax + b ) n

(a + x )(b + x ) + (a b ) ln

(a x )(b + x ) + (a + b )arcsin

dx

dx

dx =

a+ x + b+ x +C

x+b
+C
a+b

xa
+C
ba

x+b

m+ n
n
(ax + b ) n + C
(m + n )a

12.

n 1

dx

(a + bx + cx )

1
dx
b 2 + 4ac + 2cx b
ln
=
a + bx cx2 b2 + 4ac b2 + 4ac 2cx + b + C

1.
2.
3.
4.
5.
6.
7.
8.
9.
10.

ax
+C
ln a
x
x
e dx = e + C

x
a dx =

e ax
+C
a
sin x dx = cos x + C
ax
e dx =

sin ax dx = a cos ax + C
cos x dx = sin x + C
1
cos ax dx = a sin ax + C
tg x dx = ln cos x + C
1

tg ax dx = a ln cos ax + C
ctg x dx = ln sin x + C
1

11.

ctg ax dx = a ln sin ax + C

12.

cos x = sec x dx = ln sec x + tg x + C = ln tg 4 + 2 + C

13.

cos ax = a ln tg 2

14.

sin x = cosec x dx = ln(cosec x ctg x ) + C = ln tg 2

15.

sin ax dx = a ln tg

16.

cos

dx

dx

ax

+C
4

dx

dx

dx
2

ax
+C
2

= sec 2 x dx = tg x + C

dx
1
= tg ax + C
2
ax a
dx
18.
= cosec 2 x dx = ctg x + C
2
sin x
dx
1
19. 2 dx = ctg ax + C
sin ax
a
20. sec x tg x dx = sec x + C

cos

21.

cosec x ctg x dx = cosec x + C

x 1
sin 2 x + C
2 4
1
x
23. sin 2 ax dx = sin 2ax + + C
4a
2
x 1
24. cos 2 x dx = + sin 2 x + C
2 4
1
x
25. cos 2 ax dx =
sin 2ax + + C
4a
2

sin

17.

22.

x dx =

+C

tg ax
x+C
a
ctg ax
27. ctg 2 ax dx =
x+C
a
sin n1 x cos x n 1
28. sin n x dx =
+
sin n2 x dx
n
n
,

26.

tg

ax dx =

sin x dx

sin 2 x dx ( , n ), .

12.4. 12.22.

sin n1 ax cos ax n 1
29. sin ax dx =
+
sin n2 ax dx

na
n
, sin ax dx
n

sin

ax dx ( , n ),

. 12.5. 12.23.
cos n1 x sin x n 1
30. cos n x dx =
+
cos n2 x dx

n
n
,

cos x dx

cos 2 x dx ( , n ), .
12.6. 12.24.
31.

cos n1 ax sin ax n 1
+
cos n2 ax dx
na
n
, cos ax dx
n
cos ax dx =

cos

ax dx ( , n ),

. 12.7. 12.25.
tg n1 ax
n
32. tg ax dx =
tg n2 ax dx , n > 1
a(n 1)
,

tg

tg ax dx

ax dx ( , n ), .

12.9. 12.26.
33.

n
ctg ax dx =

ctg n1 ax
ctg n2 ax dx , n > 1
a(n 1)

, ctg ax dx

ctg

ax dx ( , n ),

. 12.11. 12.27.
dx
dx
1 cos x n 2
34. n =
+
n 1

n 1 sin x n 1 sin n2 x
sin x
,

35.

dx

n ,

sin x , n ( 12.14.)

dx
1
cos ax n 2
dx
+
dx =
n
n 1

ax
a(n 1) sin ax n 1 sin n2 ax

sin

dx ,

,

36.

dx
n

dx

40.

41.

42.
43.

44.

45.
46.
47.

48.

n ,

1
sin ax
dx
n2
dx
=
+
n
n 1

ax a(n 1) cos ax n 1 cos n2 ax

cos

39.

dx ,

cos x , n ( 12.12.)

38.

n ,

sin ax , n ( 12.15.)

n2
dx
1 sin x
+
n 1

x n 1 cos x n 1 cos n2 x
,

cos

37.

dx

dx ,

dx

dx ,

n ,

cos ax , n ( 12.13.)

cos n+1 x
+C
n +1
sin n+1 x
n
sin
x
cos
x
dx
=
+C

n +1
cos m1 x sin m+1 x m 1
m
n
+
cos m2 x sin n x dx , m < n
cos x sin x dx =

m+n
m+n
, ( m
) ( m ). . 12.28.,
12.39.
sin n1 x cos m+1 x n 1
m
n
=

+
x
x
dx
cos
sin
cos m x sin n2 x dx , m > n

m+n
m+n
, ( n
) ( n ). . 12.30.,
12.38.
sin (m + n )x sin (m n )x
sin mx sin nx dx = 2(m + n ) + 2(m n ) + C , m n
sin (m + n )x sin (m n )x
cos mx cos nx dx = 2(m + n ) + 2(m n ) + C , m n
cos(m + n )x cos(m n )x
2(m + n ) 2(m n ) + C , m n
sin mx cos nx dx = 1 2

sin mx + C , m = n
2m
1
1
x sin ax dx = a x cos ax + a 2 sin ax + C
1
1
x cos ax dx = a x sin ax + a 2 cos ax + C
xn
n
n
x
ax
dx
sin
=

cos ax + x n1 cos ax dx

a
a
,
12.46.
xn
n
n
x
ax
dx
cos
=
sin ax x n1 sin ax dx

a
a
,
12.45.
n
sin x cos x dx =

49.

50.

51.

52.
53.
54.

55.

a b
x
arctg
tg + C , a > b
a b
a+b 2
x
b a tg + b + a
1
dx
2
+ C , a < b
a + b cos x = b 2 a 2 ln
x
b a tg b + a
2

b c ax
2
arctg
tg + C , b 2 > c 2

2
2
2
a b c
b+c
dx
=
b + c cos ax 1
c + b cos ax + c 2 b 2 sin ax

ln
+ C , b 2 < c 2

2
2
b + c cos ax
a c b
dx
1 ax
1 + cos ax = a tg 2 + C
dx
ax
1
1 cos ax = a ctg 2 + C
x
a tg + b
dx
2
a + b sin x = a 2 b2 arctg a 2 2 b2 + C , a > b
x
a tg + b b 2 a 2
dx
1
+ C , a < b
a + b sin x = b2 a 2 ln 2x
2
2
a tg + b + b a
2
dx

a + b cos x =

b c ax
2
arctg
tg + C , b 2 > c 2

2
2
a b c
b + c 4 2
dx
=

56.
b + c sin ax
c + b sin ax + c 2 b 2 cos ax
1
ln
+ C , b 2 < c 2

2
2
b + c sin ax
a c b
dx
1 ax

1 + sin ax = a tg 4

+C
2
dx
1
ax
58.
= ctg + C
1 sin ax a
4 2
dx
1
b tg x
59. 2
=
arctg
+C
2
2
2
a cos x + b sin x ab
a

57.

60.
61.
62.
63.
64.
65.

e x (sin x cos x )
+C
e sin x dx =
2
e ax (a sin nx n cos nx )
ax
=
e
sin
nx
dx
+C

a 2 + n2
e x (sin x + cos x )
x
cos
e
x
dx
=
+C

2
e ax (n sin nx + a cos nx )
ax
=
e
cos
nx
dx
+C

a 2 + n2
e ax
ax
(
)
e sin x + dx = a 2 + 2 [a sin (x + ) cos(x + )] + C
e ax
ax
(
)
[a cos(x + ) + sin (x + )] + C
e
x
dx
cos

a2 + 2
x

66.
67.

sin ln x dx = 2 (sin ln x cos ln x ) + C

x
cos ln x dx = (sin ln x + cos ln x ) + C
2

ax

e
(ax 1) + C
a2
x ne ax n n1 ax
69. x ne ax dx =
x e dx
a
a
, x ;
12.68.
xa mx
a mx
70. xa mx dx =

+C
m ln x m(ln a )2

68.

xe

ax

dx =

a mx x n
n

a mx x n1 dx

n ln a m ln a
, x ;
12.70.
e ax cos n1 x(a cos x + n sin x ) n(n 1) ax
ax
n
72. e cos x dx =
e cos n2 x dx
+ 2
2
2
2
a +n
a +n
, ( n )
( n ).
. 12.63.
73. sh x dx = ch x + C

71.

n mx
x a dx =

74.

ch x dx = sh x + C
th x dx = ln ch x + C
cth x dx = ln sh x + C
sch x dx = 2 arctg e + C

75.
76.
77.
78.
79.
80.
81.
82.
83.
84.

csch x dx = ln th 2 + C
sch x dx = th x + C
csch x dx = cth x + C
sch x th x dx = sch x + C
csch x cth x dx = csch x + C
x 1
sh x dx = 2 + 4 sh 2 x + C
2

ch

x dx =

x 1 2
+ sh 2 x + C
2 4

13.
, .
, ,
ln x
,
log a x =
ln a
.

1.

ln x dx = x ln x x + C

2.

x ln x = ln ln x + C

3.

4.

dx

ln x
1

ln x dx = x n+1
+C
2
n + 1 (n + 1)
n
n
n 1
ln x dx = x ln x n ln x dx
n

, ln x dx ,

5.

6.
7.

13.1.
x m+1 n
m
m
n
m
n 1
x ln x dx = m + 1 ln x m + 1 x ln x dx
, 13.3.
ln 2 x
ln x
dx
=
+C
x
2
ln n x
ln n+1 x
x dx = n + 1 + C

14.
x

1.

arcsin a dx = x arcsin a +

a2 x2 + C

2.

arccos a dx = x arccos a

a2 x2 + C

3.
4.
5.
6.
7.
8.

x

+ x2 + C

arcctg a dx = x arcctg a + 2 ln(a

+ x2 + C

x2 a2
x
x x 2
2
x arcsin a dx = 2 4 arcsin a + 4 a x + C , a > 0
x2 a2
x
x x 2
arccos
x
dx
=
a x 2 + C , a > 0
arccos

a
2
4
4
a

x ax
+C
a 2
1 2
x
x ax
2
x arcctg a dx = 2 (x + a ) arcctg a + 2 + C
1

x arctg a dx = 2 (x

+ a 2 arctg

1.
2.
3.
4.

() ........................................................................3
, a + bx ( b 0 ) .............................................3
, a 2 + x 2 , a 2 x 2 , a + bx 2 .........................................................4
, a + bx . ...................................................................................5

5.

x 2 + a 2 ..................................................................................5

6.

a 2 x 2 ..................................................................................6

7.

x 2 a 2 ..................................................................................7

8. , 2ax x 2 , 2ax + x 2 .............................................................8

9. , a + bx + cx 2 ( c > 0 ) ..................................................................8
10.
, a + bx cx 2 ( c > 0 ) ..............................................................9
11.
.............................................................................9
12.
....................................................9
13.
....................................................................................14
14.
..............................................................15
..........................................................................................................................16